Should clauses prohibiting assignment be overridden by statute? - Gullifer, L (Hart Publishing, 2016)
Many contracts for the supply of goods or services include a clause prohibiting assignment by the supplier of its rights under the contract. The existence of such clauses, both in particular contracts and more generally, can have a chilling effect on the use of receivables as collateral to obtain financing. Thus, in many jurisdictions, there is a legislative override for such clauses, so that they are not enforceable against third parties. There is an ongoing debate as to whether English law should follow suit and, if so, what form the override should take, which has now led to a power to make reforms being included in sections 1 and 2 of the Small Business, Enterprise and Employment Act 2015. This chapter examines the arguments for and against an override in English law, informed by two small-scale surveys undertaken by the author and others over the last four years. Many contracts for the supply of goods or services include a clause prohibiting assignment by the supplier of its rights under the contract. The existence of such clauses, both in particular contracts and more generally, can have a chilling effect on the use of receivables as collateral to obtain financing. Thus, in many jurisdictions, there is a legislative override for such clauses, so that they are not enforceable against third parties. There is an ongoing debate as to whether English law should follow suit and, if so, what form the override should take, which has now led to a power to make reforms being included in sections 1 and 2 of the Small Business, Enterprise and Employment Act 2015. This chapter examines the arguments for and against an override in English law, informed by two small-scale surveys undertaken by the author and others over the last four years.